Heat Transfer Enhancement using Nanofluids for Cooling Computer Device: A Review - hudhaifa taha ali; Adnan M. Hussein; Jawdat A. Yagoob (NTU Journal of Engineering and Technology)
Computer heat dissipation is increasing constantly. This paper discusses a review of computer cooling methods to find the best cooling system. It can be starting with the traditional computer cooling system utilized air then developing it to a liquid cooling system. In the last decade, the nanofluid is attended potentially as a tool for cooling devices especially cooling of computer. It can be summarized the hot topic of cooling devices using nanofluid. The volume fraction and size diameter of nanofluid are significant parameters for utilizing nanofluid with cooling device.